2011
DOI: 10.1007/s11064-011-0473-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Normobaric Hyperoxia on Oxidative Stress in Mitochondria of the Guinea Pig Brain

Abstract: Normobaric hyperoxia (NBO) is applied for treatment of various clinical conditions related to hypoxia, but it can potentially also induce generation of reactive oxygen species, causing cellular damage. In this study, we examined the effects of 60 h NBO treatment on lipid and protein oxidative damage and activity of superoxide dismutase (Mn-SOD) in brain mitochondria of guinea pigs. Despite significant stimulation of Mn-SOD expression and activity the NBO treatment resulted in accumulation of markers of oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Hyperoxia has been long known to increase the generation of reactive oxygen species (Jamieson et al, 1986), which could cause oxidative damage to lipids and proteins (Tatarkova et al, 2011). Reactive oxygen species may in turn decrease enzymatic activities in aerobic metabolism pathways via inhibition of pyruvate dehydrogenase (Bogaert et al, 1994), a critical enzyme in transforming pyruvate into acetyl-CoA for the citric acid cycle.…”
Section: Physiological Considerationsmentioning
confidence: 99%
“…Hyperoxia has been long known to increase the generation of reactive oxygen species (Jamieson et al, 1986), which could cause oxidative damage to lipids and proteins (Tatarkova et al, 2011). Reactive oxygen species may in turn decrease enzymatic activities in aerobic metabolism pathways via inhibition of pyruvate dehydrogenase (Bogaert et al, 1994), a critical enzyme in transforming pyruvate into acetyl-CoA for the citric acid cycle.…”
Section: Physiological Considerationsmentioning
confidence: 99%
“…21 Several factors can account for these conflicting results, which include timing and the duration of oxygen therapy. 25 Tatarkova et al 26 demonstrated that prolonged NBO treatment is accompanied by a significant increase in mitochondrial oxidative damage. This is consistent with findings that prolonged exposure to hyperoxia can activate apoptosis.…”
Section: Strokementioning
confidence: 99%
“…•+ ) for 60 h as described previously (Tatarkova et al 2011). The O 2 concentration was monitored periodically by an oxygen analyzer (Permolyt 3, Veb Junkalor, Germany).…”
Section: Animals and Nbo Treatmentmentioning
confidence: 99%
“…The molecular mechanisms responsible for side effects of hyperoxia are not yet fully understood, however, excessive formation of reactive oxygen species (ROS) has been proposed as one of potential factors mediating damaging effects (Narkowicz et al 1993). In animal studies, it was shown that oxygenation treatment significantly increases lipid and protein oxidative damage in the heart, brain and other organs and tissues (Hensley et al 1995;Chavko and Harabin 1996;Ay et al 2007; Kaplan et al 2009;Tatarkova et al 2011). However, few studies that have investigated the efficacy of antioxidant treatment are controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation